2014
DOI: 10.1103/physreve.90.042140
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and quantumness of excitation energy transfer through a complex quantum network

Abstract: Understanding the mechanisms of efficient and robust energy transfer in organic systems provides us with new insights for the optimal design of artificial systems. In this paper, we explore the dynamics of excitation energy transfer (EET) through a complex quantum network by a toy model consisting of three sites coupled to environments. We study how the coherent evolution and the noiseinduced decoherence work together to reach efficient EET and illustrate the role of the phase factor attached to the coupling c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In this article, we have ignored decoherence, for example caused by intramolecular vibrations, although decoherence and vibrations frequently play a crucial role in transport [49][50][51][52][53][54][55][56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…In this article, we have ignored decoherence, for example caused by intramolecular vibrations, although decoherence and vibrations frequently play a crucial role in transport [49][50][51][52][53][54][55][56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…Therein, efficient light harvesting process, which delivers the captured photon energy to the reaction center, plays a crucial role in natural photosynthesis [1][2][3][4]. Because a series of experimental and theoretical explorations [5][6][7][8][9] have demonstrated that quantum coherent phenomena might exist and even optimize the natural photosynthesis, much effort has been made to reveal the effect of quantum coherence on efficient light harvesting [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on environment-assisted quantum transport (ENAQT) in pigment-protein molecular aggregates [7][8][9][10][11][12][13][14][15][16][17][18][19] have, among others, proposed the following mechanisms for an enhanced EET efficiency:…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic complexes are known to convert excitation energy to chemical energy with high efficiency [6] which has created an interest in studying their properties and trying to mimic their features in artificial photosynthesistechnology. It is believed that quantum coherence together with environmental effects enables such an efficient excitation energy transfer (EET) among the pigments in the network and many studies have tried to reveal how quantum coherence, different environmental interactions and EET efficiency are related to each other [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%